Life undercover : coming of age in the CIA - Fox, Amaryllis (New York: Alfred A. Knopf, 2019)
"Amaryllis Fox's riveting memoir tells the story of her ten years in the most elite clandestine ops unit of the CIA, hunting the world's most dangerous terrorists in sixteen countries while marrying and giving birth to a daughter"--
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: United States. -- Central Intelligence Agency -- Officials and employees -- Biography; Terrorism -- Prevention -- Government policy -- United States; Women intelligence officers -- United States -- Biography; Intelligence officers -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Military; BIOGRAPHY & AUTOBIOGRAPHY / Women; TRUE CRIME / Espionage